2020
DOI: 10.1016/j.joca.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Infrapatellar fat pad abnormalities are associated with a higher inflammatory synovial fluid cytokine profile in young adults following ACL tear

Abstract: Objective: To evaluate the degree of knee fat pad abnormalities after acute anterior cruciate ligament (ACL) tear via magnetic resonance fat pad scoring and to assess cross-sectionally its association with synovial fluid biomarkers and with early cartilage damage as quantified via T1r and T2 relaxation time measurements. Design: 26 patients with acute ACL tears underwent 3T MR scanning of the injured knee prior to ACL reconstruction. The presence and degree of abnormalities of the infrapatellar (IPFP) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 47 publications
0
39
1
Order By: Relevance
“…Synovitis can also be assessed indirectly on NCE-MRI by using the synovial proliferation score. Our group reported the synovial proliferation score as a synovial inflammation marker in young healthy patients with acute ACL rupture and results showed no significant association with average T 2 value and synovial fluid biomarkers obtained at the time of surgery [15]. However, this study showed that synovial proliferation scores at the knee were positively correlated with T 2 values, meniscus and cartilage maximum WORMS grades.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Synovitis can also be assessed indirectly on NCE-MRI by using the synovial proliferation score. Our group reported the synovial proliferation score as a synovial inflammation marker in young healthy patients with acute ACL rupture and results showed no significant association with average T 2 value and synovial fluid biomarkers obtained at the time of surgery [15]. However, this study showed that synovial proliferation scores at the knee were positively correlated with T 2 values, meniscus and cartilage maximum WORMS grades.…”
Section: Discussioncontrasting
confidence: 58%
“…Interestingly, synovial proliferation in popliteal cysts also showed significant and positive correlations with T 2 values and meniscus lesions by WORMS. One potential explanation for the synovial fluid biomarker findings in the previous ACL tear study [15] could be that synovial proliferation scores measure a chronic change that needs a longer time to develop, so synovial proliferation on MRI would be well demonstrated in a chronic process such as OA rather than in an acute trauma setting. It should also be noted that a previous study showed that synovial thickening detected on NCE-MRI of the knee corresponded to mild chronic synovitis on histo-pathology [52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since these Authors did not analyze IFP and synovial membrane inflammatory cytokines expression, it is not possible to discern the contribution of each joint tissue in the secretion of these inflammatory markers [40].…”
Section: Discussionmentioning
confidence: 99%